Mechanistic investigations of a stable, highly active, extremely sterically shielded molecular gold catalyst - Weber, Simone G.; Zahner, David; Rominger, Frank; Straub, Bernd Franz (ChemCatChem, 2013)
An N-heterocyclic carbene gold complex IPr**AuNTf2 has been synthesized, spectroscopically investigated, structurally characterized, and used as a highly active and stable catalyst in the Hashmi phenol synthesis (IPr**=1,3-di-p-tolylimidazol-2-ylidene with four di-tert-butylbenzhydryl ortho substituents, Tf=trifluoromethansulfonyl). A side reaction comprises an irreversible arene oxide ring opening with subsequent 1,2 methyl shift. The advantage of the steric demand of the ancillary ligand was explained by higher equilibrium concentrations of the cationic gold species, the circumvention of inactive dinuclear intermediates, and the inhibition of catalyst decomposition pathways. The methanol addition-hydration of alkynes featured a turnover-limiting proton transfer step of an alkenylgold catalyst resting state, indicated by a large primary kinetic isotope effect and an alkyne competition experiment.
Gesehen am 04.10.2021